Chemical Composition, Antioxidant and Antibacterial Activity of , , and Rose Water on Multidrug-Resistant Species - Farhad Sharafati Chaleshtori MSc; Mohamad Saholi BSc; Reza Sharafati Chaleshtori PhD (SAGE Publishing, 2018)
This research was aimed at investigating the antioxidant and antibacterial activity of Bunium persicum , Eucalyptus globulus , and rose water on multidrug-resistant Listeria species. The antibiotic resistance of Listeria spp obtained from seafood samples were determined by the Kirby-Bauer method. The antioxidant and antibacterial activity of the essential oils and extracts were evaluated using ferric reducing antioxidant power and microdilution methods, respectively. A total 2 samples (1.88%) were positive for Listeria spp. L monocytogenes was found to be resistant to ampicillin, amoxicillin/clavulanic acid, penicillin, vancomycin, and kanamycin. B persicum essential oil showed the greatest antioxidant activity (248.56 ± 1.09 µM Fe 2+ /g). The E globulus essential oil showed consistently strong antimicrobial activity against L monocytogenes and L grayi , while rose water showed no antimicrobial activity against any of the tested bacterial strains. The results showed that after adding the B persicum and E globulus essential oils to bacteria, the cell components' release increased significantly.